SiMoVA: sistema de monitorização de variáveis ambientais - Matos, Rui (1998)
This paper describes an open and configurable system to perform continuous monitoring of environmental variables. The system is based on a client/ server architecture. The remote stations where built with PLCs (Programmable Logic Controllers) and the server is a PC, containing a software package developed in Labview (Virtual Laboratory Instrument Engineering Workbench) and running under Windows.